Dietary regimens for chronic hepatic diseases: advice and compliance (Italian Journal of Public Health, 2011)
Background: Nutrition is coming to the fore as a major determinant of chronic diseases, and scientific evidence supports this view. The link between diet and chronic liver disease is an important area of study, as it could help reduce the suffering and the economic burden caused by liver disease. The study aimed to assess the current dietary guidelines of chronic hepatic disease patients and to determine their compliance and that of service providers to following these guidelines.Methods: A cross sectional descriptive study was conducted in the inpatient section of one of Cairo’s University hospitals in Egypt for a duration of 12 months. Interviewing questionnaires were used to collect the required data from 60 patients and 20 service providers. The objective of the study was adequately explained to participants and their consensus was obtained with assured confidentiality.Results: The majority of patients (73.5%) received dietary advice from hospital physicians only or in conjunction with their private physician. The advice was given orally by 100% of hospital physicians though only by 21% of private physicians which could have negatively affected patients’ compliance. About 60 % of the patients claimed to be compliant with the dietary regimens prescribed. Non compliance was related to lack of supportive measures  52.2%) or to negative patient attitude (48.8%). Hospital meals were not satisfactory neither to the service providers nor to clients. Hospital physicians did not properly prescriberegimens for reasons related to insufficient knowledge (66.7%), patients' attitudes (20%) and patients’ overload (13.3%).Conclusions: A standardized comprehensive set of dietary guidelines for different liver disease patientsshould be developed and communicated to service providers so as to promote compliance amongst patients.
Keywords: dietary regimen; hepatic diseases; compliance; advice